Nomadic pastoralists' experience accessing reproductive and maternal healthcare services in low and middle-income countries: A contextual scoping review - Joseph Kwame Wulifan; Amos Dangbie Dordah; Joshua Sumankuuro (Pastoralism, 2022)
Abstract Globally, discriminately vulnerable and marginalized groups, such as nomadic pastoralist populations, have perhaps the least access to reproductive and maternal health services (R/MHCSs). Previous studies report that most nomadic pastoralist mothers use both traditional methods of childbirth (i.e. delivering at home and assistance by traditional birth attendants (TBAs)) and traditional methods of contraception. However, determining factors of R/MHCSs in these nomadic pastoralist communities remain scarcely explored and condensed. This study aims to analyse quantitative, qualitative, and mixed methods studies and summarize pastoralists’ experience accessing R/MHCSs in low- and middle-income countries (LMICs). We employed a mixed method approach in conducting this scoping review by including studies applying quantitative, qualitative, and mixed methods retrieved from online databases (PubMed, Google Scholar, and JSTOR) as well as reviewing indexes of journals specific to the field by using a set of keywords related to R/MHCSs in LMICs. Thematic content analysis was performed to generate four themes and codes. We retrieved 2131 articles and retained 25 that met our inclusion criteria. Of these, 6 were quantitative studies, 12 were qualitative studies, and 7 were mixed methods studies. We found that nomadic pastoralists face multi-faceted barriers in access to R/MHCS that can be broadly categorized into four themes: (i) physical (geographic isolation and access), (ii) political (discriminatory/marginalized status, poor transport system, lack of infrastructure, and little political status to improve their lives), (iii) economic (poor quality of service/lack of available resources in rural areas where nomadic pastoralists live, vulnerability, poverty/affordability of R/MHCSs), and (iv) socio-cultural (misconceptions, perception, gender roles in decision-making, low demand for R/MHCSs by nomadic pastoralists, autonomy for females to travel) factors. Therefore, to effectively address the needs of nomadic pastoralist populations, R/MHCSs must be available, accessible, acceptable, and affordable through political, economic, geographic, and socio-culturally sensitive approaches. Low awareness of, and low access to, modern R/MHCSs and their benefits is a critical barrier to service utilization. Partnership with nomad communities through leveraging existing structures, networks, and decision-making patterns and involvement of nomadic women and girls, community leaders, male partners, and trained traditional birth attendants are key to R/MHCS access. What is known about this topic? 1. The utilization of a skilled attendant at birth has been improving amongst nomadic pastoralists but with significant variations across LMICs. 2. The experiences in accessing R/MHCs amongst pastoralist populations are not fully known. What the study adds 1. Traditional delivery beds should be provided in health facilities because most nomadic women believe the sitting position during delivery speeds up the labour. 2. Static health facilities are not helpful for pastoralist lifestyles because they are inaccessible and culturally insensitive. 3. Female midwives are required in the health facilities to attract pastoralist women who abhor being attended to by male midwives. We also call for the need for culturally appropriate maternal care at healthcare facilities. 4. Conventional youth programming does not reach the large population of marginalized and disadvantaged nomadic girls who need reproductive health information and services. Innovative approaches considering the socio-cultural and economic environment can better address the nomadic youth’s reproductive health challenges. 5. In order to increase girls’ participation in reproductive health issues, it is important to create a safe environment for them and to involve their mothers in issues of sexual and reproductive health. 6. To successfully give nomadic girls and mothers a voice in their reproductive health requires the support of cultural leaders who give direction on various issues in the community. 7. Safe spaces and social networks for girls are potent strategies for RH advocacy at the community level. 8. Accessing FP methods is a problem mainly due to long distances to health facilities. 9. Some women are willing to use modern FP methods but encounter resistance from their male partners/husbands. 10. Traditional FP methods are popular because they are readily available, have no side effects, and are trusted.